Visions how science will revolutionize the 21st century - Kaku, Michio (Anchor Books, 1998)
Discusses the future of science and technology in the next one hundred years, drawing from interviews with scientists in a wide variety of disciplines to make predictions about developments in the fields of computer science, biogenetics, and quantum physics.